Patients with Difficult-to-Treat Depression Do not Exhibit an Increased Frequency of CYP2D6 Allele Duplication - Háber, Á.; Rideg, O.; Osváth, P.; Fekete, S.; Szücs, F.; Fittler, A.; Kovács, G. L.; Miseta, A.; Botz, L. (Pharmacopsychiatry, 2013)
The insufficient response of patients to antidepressant medications may result from several factors, including altered drug metabolism. CYP2D6 genotyping may help assess the possible factors that contribute to difficult-to-treat depression. The aim of our study was to determine the frequency of CYP2D6 allelic variants and the prevalence of predicted CYP2D6 phenotypes in patients who were suffering from difficult-to-treat depression and compare the data with those for the healthy population of Hungary.55 patients who failed to respond to 2 or more adequate trials of different CYP2D6-dependent antidepressants were selected for genotyping.The prevalence of the predicted CYP2D6 phenotypes in the patient population was 1.8% for the UMs, 80.0% for EMs, 3.6% for IMs and 14.5% for PMs compared with 1.9% for UMs, 83.3% for EMs, 6.5% for IMs and 8.3% for PMs in the Hungarian population.The CYP2D6 allele frequencies and the predicted phenotype distributions in patients with difficult-to-treat depression were not significantly different to those found in the healthy population of Hungary. The cumulative frequency of the CYP2D6*1XN, *2XN and *35XN alleles was 0.9% in the patient population suggesting that CYP2D6 duplication or multiplication does not play a significant role in antidepressant pharmacotherapy failure in this patient sample. The cumulative frequency of the non-functional alleles (33.5%) and the prevalence of the genetically determined PM phenotype (14.5%) were relatively high in the patient group. These figures draw attention to the possibility of unrecognised and non-reported side effects and non-adherence to drug treatment.
Keywords: major depressive disorder; difficult-to-treat depression; CYP2D6 genotyping; CYP2D6 allele duplication; ultrarapid metaboliser phenotype